Liaison librarian programs as described on U.S. college and university library websites - Arendt, Julie; Peacemaker, Bettina (The Journal of academic librarianship, 2023)
Case studies and surveys describing roles of liaison librarians and structure of liaison librarian programs have generally focused on libraries at large, research-oriented universities. This study was conducted to better understand the role of liaison librarians and the structure of liaison programs across more types of college and university libraries. Listings of liaison librarians on library websites at institutions with a wide range of enrollments were examined. Document analysis was used to observe how common it was for libraries to have such listings, how many liaison librarians were listed, what title was used for the position, what services were described, and if library employees not matched to university departments were also included in the list. Although there was substantial overlap in how institutions described their liaison librarian services, smaller and larger institutions had some noteworthy differences. Over 80 % of institutions with >5000 full-time equivalent (FTE) students had a liaison librarian listing on the library website, while less than half of smaller institutions had a listing. The largest institutions also tended to have more liaison librarians, frequently included subject specialization in liaison titles, and offered non-departmental services in their listings more often than smaller institutions.